2013
DOI: 10.1108/cb-07-2012-0033
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of library use, collections and services among the students of engineering: a case study of King Saud University

Abstract: PurposeThe purpose of this paper is to examine the determinants of library use, collections and services among the students of engineering at King Saud University, Riyadh (KSA).Design/methodology/approachA survey was designed to collect needed information about the level of usage of library collections, services and satisfaction of users. A well‐structured questionnaire was circulated among the faculties, research scholars, postgraduates, undergraduates, and other categories to collect the necessary primary da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…However, the such statements should be made carefully because it is not possible to give an unambiguous answer to the question of whether students prefer printed or electronic sources. There are still many students who prefer printed sources (Boumarafi, 2010;De Oliveira, 2012;Hamade & Al-Yousef, 2010;Hussain & Abalkhail, 2013;Rockinson-Szapkiw, Courduff, Carter, & Bennett, 2013;Shepperd, Grace, & Koch, 2008;Shuling, 2007;Swain, 2010;Woody, Daniel, & Baker, 2010). One of the reasons why students report that printed sources, such as books, have a better reputation and contain more basic and well established facts is that the Internet holds a great deal of irrelevant and inaccurate information that makes the search difficult (Griffiths & Brophy, 2005;Nkomo, Ocholla, & Jacobs, 2011;Ozoemelem, 2009;Sujatha & Mudhol, 2008;Wu & Chen, 2012;Yu-Mei & Artero, 2005).…”
Section: Students' Perceptions Of Electronic Resourcesmentioning
confidence: 95%
“…However, the such statements should be made carefully because it is not possible to give an unambiguous answer to the question of whether students prefer printed or electronic sources. There are still many students who prefer printed sources (Boumarafi, 2010;De Oliveira, 2012;Hamade & Al-Yousef, 2010;Hussain & Abalkhail, 2013;Rockinson-Szapkiw, Courduff, Carter, & Bennett, 2013;Shepperd, Grace, & Koch, 2008;Shuling, 2007;Swain, 2010;Woody, Daniel, & Baker, 2010). One of the reasons why students report that printed sources, such as books, have a better reputation and contain more basic and well established facts is that the Internet holds a great deal of irrelevant and inaccurate information that makes the search difficult (Griffiths & Brophy, 2005;Nkomo, Ocholla, & Jacobs, 2011;Ozoemelem, 2009;Sujatha & Mudhol, 2008;Wu & Chen, 2012;Yu-Mei & Artero, 2005).…”
Section: Students' Perceptions Of Electronic Resourcesmentioning
confidence: 95%
“…The size of the sample taken was quite large, so that the formalities of identification can be assisted. This method has been adopted by Hussain and Abalkhail (2013) and Kumar et al (2010) in their studies. Moreover, this was done with to obtain result-oriented findings and make inferences generally.…”
Section: Methodsmentioning
confidence: 99%
“…Some of the relevant studies in chronological order are as follows: Hussain and Abalkhail (2013) examined the determinants of library use, collections and services among the students of engineering at King Saud University, Riyadh (KSA). The findings of the study revealed that a majority of the users used the circulation service.…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations